The behavior of heavy metals in the process of desulfurization of brazilian coal combustion gases by the addition of limestone - Sebag, Maria da Graca (2013)
The concentrations of heavy metals in two kinds of Brazilian coals at 100° C (acid digestion) and at 850° C were studied (ashes the obtained in muffle furnace with and without addition of limestone). Data were analyzed by flame atomic absorption, using the air acetylene flame. For Pb, Zn, Ni, Mn and Cu the metal concentration obtained the acid digestion were higher than metal concentration were obtained in tests in the muffle furnace. This behavior observed in the muffle furnace occurs because these metals are fixed in stable sulfated compounds in the ashes, which are difficult to dissociate at flame temperature, and also due to the volatile character of the metals, mainly Pb and Zn. There was a constant concentration in the ashes in of Cr the acid digestion and muffle furnace tests. Results from tests using an XRD apparatus indicated, he formation of sulfated compounds in the ashes for both. coals. The analysis using microprobe electronic showed retention of metals like Ni, Mn, Cu, Fe, Ti and Ca. For both coals, the low mobility of most of the metals studied occured due to the alkaline pH of sulfated ashes. These metals in the ash from coal combustion in fluidized bed reactor were also studied and showed similar results, enabling a scale-up to pilot scale.